2017
DOI: 10.1016/j.elecom.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Pt oxide and oxygen reduction at Pt(111) studied by surface X-ray diffraction

Abstract: The influence of the oxygen reduction reaction on the oxidation of Pt(111) is studied by surface X-ray diffraction. The oxygen reduction reaction does not significantly influence the place-exchange process during the initial stages of oxidation and there is no change in the onset potential and kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Figure 5a shows the stepwise oxidation of a single layer of Nafion-supported nanoparticles. The onset potential for oxide formation lies between 0.9 V RHE and 1.15 V RHE (in agreement with the literature 10,13−19 ), roughly 0.2 V lower than for Pt/FAD. Note that this shift in oxidation onset is also present for thicker Pt layers on Nafion.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 5a shows the stepwise oxidation of a single layer of Nafion-supported nanoparticles. The onset potential for oxide formation lies between 0.9 V RHE and 1.15 V RHE (in agreement with the literature 10,13−19 ), roughly 0.2 V lower than for Pt/FAD. Note that this shift in oxidation onset is also present for thicker Pt layers on Nafion.…”
Section: Resultssupporting
confidence: 91%
“…The importance of oxygen in the dissolution process suggests that platinum oxides are involved. Indeed, it was shown that the surface of Pt cathodes is (partially) oxidized at ORR potentials, particularly in the presence of oxygen. , …”
Section: Introductionmentioning
confidence: 99%
“…Conventional SXRD studies were performed at beamline ID03 and focused on kinetic studies of the Pt oxidation process by measuring the X-ray intensity at a fixed position along a crystal truncation rod (CTR). Similar as in our previous studies, 17,18,23,24,40 these measurements employed a photon energy of 22.5 keV, a (vert./hor.) beam size of 45×750 µm 2 and an angle of incidence of 0.3 • .…”
Section: Surface X-ray Diffraction Setupmentioning
confidence: 90%
“…It has been shown that carefully designed Pt NPs would rapidly evolve to thermodynamically equilibrated shapes and sizes with similar activities, regardless the initial shape or size, because of the potential induced dissolution/re-deposition of Pt atoms at potentials close to E onset ORR [32,[52][53][54][55]. Apparently, this process is not modified by the presence of oxygen in the electrolyte [56][57][58], and then, it would be inherent to the nature of the electrolyte and the electrode. Hence, strategies are needed to increase the stability of these NPs, such as the approaches already effectively attempted on metal-Pt alloys [32,53,59,60], and Pt stepped surfaces by modifying the surface by selective deposition of stable adatoms [61], which have increased the stability of these surfaces.…”
Section: A C C E P T E D Mmentioning
confidence: 99%